Beyond language: empathy and emotion recognition deficits in primary progressive aphasias - Giulia Giacomucci; Alice Pieri; Valentina Moschini; Chiara Crucitti; Sonia Padiglioni; Carmen Morinelli; Giulia Galdo; Filippo Emiliani; Matilde Nerattini; Silvia Bagnoli; Assunta Ingannato; Sandro Sorbi; et al. (NeuroImage: Clinical, 2025)
Although primary progressive aphasia (PPA) is considered a language disorder, increasing evidence points to the presence of social cognition impairments in PPA variants. The aims of this study were to explore empathy and emotion recognition deficits in the three PPA variants (sv-PPA, lv-PPA, nfv-PPA) and to identify their neural correlates.Eleven sv-PPA, 34 lv-PPA,11 nfv-PPA patients and 34 healthy controls (HC) were included in this study. Empathy was explored with the Interpersonal Reactivity Index (IRI) (Perspective Taking – PT, Fantasy – FT, Empathic Concern – EC, Personal Distress – PD), rated by caregivers before (T0) and after (T1) the onset of cognitive symptoms. Emotion recognition was evaluated with the Ekman 60Faces (EK-60F) Test and metabolic activity with [18F]FDG-PET.In all PPA variants, PT score was reduced from T0 to T1 (sv-PPA p = 0.014, lv-PPA p < 0.001, nfv-PPA p = 0.022) and PD score was increased (sv-PPA p = 0.033, lv-PPA p < 0.001, nfv-PPA p = 0.009). Only lv-PPA showed a decrease of FT score (p = 0.024), while EC was spared in all three variants. Sv-PPA patients had the worst performances in the EK-60F Test, followed by lv-PPA and, lastly, by nfv-PPA.Correlations between EK-60F scores and metabolic activity were found in sv-PPA and lv-PPA, highlighting the involvement of areas participating in the emotion recognition network: cingulate cortex, insula, temporal and orbitofrontal cortices and inferior frontal gyrus.All PPA variants exhibited impairments in cognitive empathy (PT) and heightened emotional contagion (PD). The most severe deficits in emotion recognition were shown by sv-PPA, while nfv-PPA was the less impaired variant.